Fireproof silicone sealant with low smoke amount and preparation method thereof
By using modified layered MgAl bimetallic hydroxide and modified nanocomposite expanded graphite in the fire-resistant sealant, a tight carbonized layer is formed, which solves the problem of fire-resistant sealant producing a large amount of smoke when burning at high temperatures, and achieves a combination of low smoke generation and high flame retardant performance.
Patent Information
- Application Number
- CN202411868805.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-03-04
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing fire-proof sealants produce a large amount of smoke when burned at high temperatures, affecting personnel evacuation and fire rescue.
A fire-resistant silicone sealant with low smoke generation is used, and its composition includes α, ω-dihydroxypolydimethylsiloxane, composite flame retardant, inorganic filler and porcelain filler, etc., through the use of modified layered MgAl bimetallic hydroxide and modified nanocomposite expanded graphite, a tight carbonized layer is formed to prevent the transfer of heat and oxygen.
It significantly reduces the combustible substances generated by the sealant during combustion, reduces the amount of smoke, improves the flame retardant effect and sealing performance, and enhances the blocking ability to heat and oxygen.
Smart Images

Figure BDA0005195219680000111 
Figure BDA0005195219680000121
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of sealants, in particular to a low-smoke-generating fireproof silicone sealant and a preparation method thereof. Background Art
[0002] As a kind of fireproof sealing material, fireproof sealant is widely used in fireproof sealing of joints, holes and other parts of buildings. When a fire occurs, fireproof sealant can effectively prevent the spread of fire and buy precious time for personnel evacuation and fire rescue. At present, most of the fireproof sealant products on the market have undergone special treatment, usually adding flame retardants, fire retardants, thickeners, curing agents and other materials to the base material to make a mixture of glue.
[0003] CN2021104991728 discloses a novel flame retardant intumescent fireproof sealant, whose flame retardant is a composite flame retardant composed of expanded graphite, liquid flame retardant, zinc borate and ceramic fiber powder. The fireproof sealant has excellent flame retardant properties and effectively blocks the spread of heat and flame. CN 118772804A discloses a composite fireproof adhesive, which originally includes an aqueous adhesive, a sodium silicate colloidal solution, expanded graphite, an endothermic powder, an inorganic filler, etc. As one of the flame retardants, expanded graphite can rapidly expand to form a carbon layer during the combustion process, isolating oxygen and heat, thereby playing a flame retardant role. CN 117965130B discloses a silicone fireproof sealant for construction. The silicone fireproof sealant for construction comprises, by weight, 100-140 parts of α, ω-dihydroxy polydimethylsiloxane, 1-5 parts of fumed silica, 15-33 parts of dimethyl silicone oil, 10-25 parts of organically modified sepiolite, 5-18 parts of composite phosphorus-containing fluxing agent, 20-45 parts of modified calcium sulfate whiskers, 0.1-1.2 parts of catalyst, 2-5 parts of co-catalyst and 5-13 parts of crosslinking agent. The organic polysilazane physically adsorbed inside the organically modified sepiolite will overflow from the sepiolite due to high-temperature expansion when the silicone glue burns. The overflowed organic polysilazane will undergo a crosslinking reaction by itself or a chemical crosslinking reaction with the silicone glue matrix at high temperature, which will further enhance the integrity and compactness of the silicone glue matrix during combustion, so as to better maintain the sealing state. CN110003844 B discloses a method for preparing a porcelain silicone sealant, the sealant comprising: 80-100 parts of α, ω-dihydroxy polydimethylsiloxane, 1-50 parts of polydimethylsiloxane, 50-100 parts of functional filler, 2-24 parts of silane coupling agent, 2-15 parts of plasticizer, 0.5-3 parts of catalyst, and 5-20 parts of water glass; the method introduces reactive functional groups by surface modification of solid fillers such as porcelain powder and flame retardant, so that it can react with the base glue to form a cross-linked network structure, thereby further improving its adhesive strength. The above patent reports do not pay attention to the smoke emission and conduct corresponding tests. At present, the fireproof sealants on the market focus more on good fireproof and flame retardant properties, and do not pay enough attention to the smoke emission. Most fireproof sealants tend to produce a large amount of smoke when burned at high temperatures, which has an adverse effect on personnel evacuation and fire rescue.
[0004] Therefore, in view of the above problems, the present invention urgently needs to provide a low smoke-generating fire-proof silicone sealant and a preparation method thereof. Summary of the invention
[0005] The purpose of the present invention is to provide a low-smoke fire-proof silicone sealant and a preparation method thereof, and to solve the problem that the existing fire-proof silicone sealant often generates a large amount of smoke when burning at high temperature, which has an adverse effect on personnel evacuation and fire rescue.
[0006] The present invention provides a low smoke-generating fireproof silicone sealant, which comprises, by weight:
[0007] 100-140 parts of α,ω-dihydroxy polydimethylsiloxane, 10-40 parts of dimethyl silicone oil, 30-80 parts of composite flame retardant, 5-20 parts of inorganic filler, 10-80 parts of ceramic filler, 0.05-0.2 parts of catalyst, 5-15 parts of crosslinking agent and 4-6 parts of silane coupling agent;
[0008] The composite flame retardant consists of modified layered MgAl double metal hydroxide and modified nano composite expanded graphite.
[0009] Preferably, the mass ratio of the modified layered MgAl double metal hydroxide to the modified nanocomposite expanded graphite is (60-80):(20-40).
[0010] Preferably, the preparation process of the modified layered MgAl double hydroxide comprises:
[0011] Mix magnesium nitrate, aluminum nitrate and ZrOCl2·8H2O solution in a molar ratio of 3:1:(1-3), heat to 80°C under a nitrogen atmosphere, control the pH to 9-10, react for 10 hours, and obtain a suspension;
[0012] The suspension was transferred to an autoclave, reacted at 600°C for 5 h, cooled to room temperature, filtered, washed, and dried to obtain Zr / MgAl-LDH;
[0013] Stearic acid and Zr / MgAl-LDH were added to deionized water with a mass ratio of 3:2. The pH was adjusted to 7. The mixture was reacted at 80° C. for 10 h. The mixture was filtered, washed, and dried to obtain a modified layered MgAl double hydroxide.
[0014] Preferably, the preparation steps of modified nano composite expanded graphite include:
[0015] The expanded graphite is washed and dried, and the dried expanded graphite is placed in a mixed solution of anhydrous ethanol and deionized water, and subjected to ultrasonic treatment to obtain a suspension;
[0016] Adding an ammonia solution to the suspension and adjusting the pH value to 8-9 to obtain an expanded graphite suspension;
[0017] Slowly drop ethyl orthosilicate into the suspension, stir and react at 55°C for 6 hours, filter and wash with ethanol until neutral, and dry to obtain nanocomposite expanded graphite;
[0018] Deionized water is added to the nano-composite expanded graphite, and the mixture is stirred to obtain a nano-composite expanded graphite slurry. A silane coupling agent is dissolved in a small amount of anhydrous ethanol, and the mixture is poured into the nano-composite expanded graphite slurry, and the mixture is stirred to obtain a modified nano-composite expanded graphite.
[0019] Preferably, the coupling agent is one of hexadecyltrimethoxysilane, dodecyltrimethoxysilane or cycloalkylsilane.
[0020] Preferably, the particle size of the expanded graphite is 200-300 μm; and the amount of ethyl orthosilicate added is 1-3 wt % of the expanded graphite.
[0021] Preferably, the mass ratio of nanocomposite expanded graphite: silane coupling agent: ethanol: aqueous solution is 1: (0.02-0.06): (0.2-0.4): (3-5).
[0022] Preferably, the inorganic filler is a modified inorganic filler, and the preparation method of the modified inorganic filler comprises:
[0023] The inorganic filler is mixed with a silane coupling agent and ethanol, stirred at a temperature of 50-60° C. for 60 minutes, filtered and dried to obtain a modified inorganic filler; wherein the mass ratio of the inorganic filler: the silane coupling agent: the ethanol is 1: (0.1-0.3): (2-5).
[0024] Preferably, the silane coupling agent is one of KH550, KH60 or KH570.
[0025] Preferably, the ceramic filler is modified glass fiber, and the treatment process of the modified glass fiber is:
[0026] After mixing glass fiber and water glass, stirring at a temperature of 50-60°C for 60 minutes, filtering and drying to obtain modified glass fiber;
[0027] Wherein, the mass ratio of glass fiber to water glass is 1:(0.1-0.3);
[0028] The particle size of the glass fiber is 0.1-10 μm.
[0029] The present invention also provides a method for preparing a low-smoke fire-resistant silicone sealant according to any one of claims 1 to 9, characterized in that it comprises the following preparation steps:
[0030] According to the weight ratio, α, ω-dihydroxy polydimethylsiloxane, dimethyl silicone oil, inorganic filler and ceramic filler are added into a planetary machine, and dehydrated for 90 to 160 minutes at 110° C. to 140° C. and a vacuum degree of -0.08 MPa to -0.1 MPa to obtain a base material;
[0031] The base material is cooled to room temperature, and a composite flame retardant, a catalyst, a cross-linking agent and a silane coupling agent are added and mixed, and stirred for 90 to 180 minutes under a vacuum degree of -0.08 MPa to -0.1 MPa to obtain a fire-resistant silicone sealant with low smoke emission.
[0032] The low-smoke-generating fireproof silicone sealant and its preparation method provided by the present invention have the following improvements compared with the prior art:
[0033] 1. The fireproof silicone sealant with low smoke emission provided by the present invention modifies layered MgAl double metal hydroxide by stearic acid and ZrOx to enhance the hydrophobicity of the inorganic flame retardant, introduces nano-SiO2 particles into the surface and interlayer of graphite sheets, and modifies the expanded graphite so that a tighter connection is formed between the graphite sheets, thereby facilitating the formation of a tighter and stronger carbonized layer during the combustion process. The modified inorganic flame retardant has a synergistic effect with the nano-expanded graphite material, has good dispersibility in the matrix, and is conducive to forming a tighter carbonized layer, hindering the transfer of heat and oxygen, further enhancing the overall flame retardant effect, and reducing the combustible substances generated by the sealant during the combustion process, thereby reducing the smoke emission.
[0034] 2. The low-smoke fireproof silicone sealant provided by the present invention can be evenly dispersed in the sealant matrix by improving the inorganic filler and the ceramic material, and has excellent thermal insulation and high temperature resistance. The addition of the modified ceramic filler makes it difficult for the combustion products to collapse, and effectively blocks toxic gases and smoke.
[0035] 3. The low-smoke fireproof silicone sealant provided by the present invention adopts specific components in specific contents to achieve better overall interaction. The product generates less smoke at high temperatures while meeting basic use requirements. DETAILED DESCRIPTION
[0036] The technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0037] The present invention provides a low-smoke fireproof silicone sealant, which is characterized by comprising, by weight:
[0038] 100-140 parts of α,ω-dihydroxy polydimethylsiloxane, 10-40 parts of dimethyl silicone oil, 30-80 parts of composite flame retardant, 5-20 parts of inorganic filler, 10-80 parts of ceramic filler, 0.05-0.2 parts of catalyst, 5-15 parts of crosslinking agent and 4-6 parts of silane coupling agent;
[0039] The composite flame retardant consists of modified layered MgAl double metal hydroxide and modified nano composite expanded graphite.
[0040] Specifically, the mass ratio of the modified layered MgAl double metal hydroxide to the modified nanocomposite expanded graphite is (60-80):(20-40).
[0041] Specifically, the preparation process of the modified layered MgAl double hydroxide includes:
[0042] Mix magnesium nitrate, aluminum nitrate and ZrOCl2·8H2O solution in a molar ratio of 3:1:(1-3), heat to 80°C under a nitrogen atmosphere, control the pH to 9-10, react for 10 hours, and obtain a suspension;
[0043] The suspension was transferred to an autoclave, reacted at 600°C for 5 h, cooled to room temperature, filtered, washed, and dried to obtain Zr / MgAl-LDH;
[0044] Stearic acid and Zr / MgAl-LDH were added to deionized water with a mass ratio of 3:2. The pH was adjusted to 7. The mixture was reacted at 80° C. for 10 h. The mixture was filtered, washed, and dried to obtain a modified layered MgAl double hydroxide.
[0045] Specifically, the preparation steps of modified nano composite expanded graphite include:
[0046] The expanded graphite is washed and dried, and the dried expanded graphite is placed in a mixed solution of anhydrous ethanol and deionized water, and subjected to ultrasonic treatment to obtain a suspension;
[0047] Adding an ammonia solution to the suspension and adjusting the pH value to 8-9 to obtain an expanded graphite suspension;
[0048] Slowly drop ethyl orthosilicate into the suspension, stir and react at 55°C for 6 hours, filter and wash with ethanol until neutral, and dry to obtain nanocomposite expanded graphite;
[0049] Deionized water is added to the nano-composite expanded graphite, and the mixture is stirred to obtain a nano-composite expanded graphite slurry. A silane coupling agent is dissolved in a small amount of anhydrous ethanol, and the mixture is poured into the nano-composite expanded graphite slurry, and the mixture is stirred to obtain a modified nano-composite expanded graphite.
[0050] Specifically, the coupling agent is one of hexadecyltrimethoxysilane, dodecyltrimethoxysilane or cycloalkylsilane.
[0051] Specifically, the particle size of the expanded graphite is 200-300 μm; and the amount of ethyl orthosilicate added is 1-3 wt % of the expanded graphite.
[0052] Specifically, the mass ratio of nanocomposite expanded graphite: silane coupling agent: ethanol: aqueous solution is 1: (0.02-0.06): (0.2-0.4): (3-5).
[0053] Specifically, the inorganic filler is a modified inorganic filler, and the preparation method of the modified inorganic filler includes:
[0054] The inorganic filler is mixed with a silane coupling agent and ethanol, stirred at a temperature of 50-60° C. for 60 minutes, filtered and dried to obtain a modified inorganic filler; wherein the mass ratio of the inorganic filler: the silane coupling agent: the ethanol is 1: (0.1-0.3): (2-5).
[0055] Preferably, the silane coupling agent is one of KH550, KH60 or KH570.
[0056] Preferably, the ceramic filler is modified glass fiber, and the treatment process of the modified glass fiber is:
[0057] After mixing glass fiber and water glass, stirring at a temperature of 50-60°C for 60 minutes, filtering and drying to obtain modified glass fiber;
[0058] Wherein, the mass ratio of glass fiber to water glass is 1:(0.1-0.3);
[0059] The particle size of the glass fiber is 0.1-10 μm.
[0060] The present invention also provides a method for preparing the low-smoke fire-resistant silicone sealant as described in any one of the above, comprising the following preparation steps:
[0061] S1) adding α,ω-dihydroxy polydimethylsiloxane, dimethyl silicone oil, inorganic filler and ceramic filler into a planetary machine according to weight ratio, and dehydrating for 90 to 160 minutes at 110° C. to 140° C. and vacuum degree of -0.08 MPa to -0.1 MPa to obtain a base material;
[0062] S2) The base material is cooled to room temperature, and a composite flame retardant, a catalyst, a cross-linking agent and a silane coupling agent are added, mixed, and stirred for 90 to 180 minutes under a vacuum degree of -0.08 MPa to -0.1 MPa to obtain a fire-resistant silicone sealant with low smoke emission.
[0063] Embodiment 1
[0064] The preparation method of low smoke-generating fireproof silicone sealant comprises the following preparation steps:
[0065] 101) Preparing a modified layered MgAl double hydroxide, the preparation process comprising:
[0066] A11) mixing magnesium nitrate, aluminum nitrate and ZrOCl2·8H2O solution in a molar ratio of 3:1:2, heating to 80° C. under a nitrogen atmosphere, controlling the pH to 9-10, reacting for 10 h, and obtaining a suspension;
[0067] A12) transferring the suspension into a stainless steel autoclave with a Teflon liner, reacting at 600° C. for 5 h, cooling to room temperature, filtering and washing for multiple times, and drying to obtain Zr / MgAl-LDH;
[0068] A13) Stearic acid and Zr / MgAl-LDH are added to deionized water in a mass ratio of 3:2, the pH is adjusted to 7, the reaction is carried out at 80° C. for 10 h, the reaction is filtered, washed, and dried to obtain a modified layered MgAl double hydroxide.
[0069] 102) preparing modified nano composite expanded graphite, the preparation steps comprising:
[0070] B11) washing expanded graphite, washing 30 parts of expanded graphite with 90 parts of deionized water to remove impurities on the surface of the expanded graphite, drying at 60° C. for 6 h, placing the dried expanded graphite in a mixed solution of anhydrous ethanol and deionized water, and ultrasonically treating to obtain a suspension;
[0071] B12) slowly adding an aqueous ammonia solution into the suspension, adjusting the pH value to 8-9, and obtaining an expanded graphite suspension;
[0072] B13) adding ethyl orthosilicate slowly dropwise to the suspension, stirring and reacting at 55° C. for 6 h, filtering and washing with ethanol several times until neutral, and drying at 60° C. for 12 h to obtain nanocomposite expanded graphite;
[0073] B14) adding deionized water to the nanocomposite expanded graphite, stirring to obtain a nanocomposite expanded graphite slurry, dissolving a silane coupling agent in a small amount of anhydrous ethanol, pouring the solution into the nanocomposite expanded graphite slurry, stirring to obtain a modified nanocomposite expanded graphite, wherein the mass ratio of the nanocomposite expanded graphite: the silane coupling agent: the ethanol: the aqueous solution is 1:0.03:0.2:3, wherein the coupling agent is hexadecyltrimethoxysilane; the particle size of the expanded graphite is 250 μm; and the amount of ethyl orthosilicate added is 1wt% of the expanded graphite.
[0074] 103) mixing the modified layered MgAl double metal hydroxide and the modified nano-composite expanded graphite to obtain a composite flame retardant, wherein the mass ratio of the modified layered MgAl double metal hydroxide to the modified nano-composite expanded graphite is 70:30;
[0075] 104) According to the weight ratio, 120 parts of α, ω-dihydroxy polydimethylsiloxane, 20 parts of dimethyl silicone oil, 10 parts of inorganic filler and 50 parts of porcelain filler are added into a planetary machine, and dehydrated for 120 minutes at 120° C. and a vacuum degree of -0.08 MPa to -0.1 MPa to obtain a base material;
[0076] 105) The base material is cooled to room temperature, 50 parts of composite flame retardant, 0.1 parts of catalyst, 10 parts of cross-linking agent and 5 parts of silane coupling agent are added, mixed, and stirred for 120 minutes under a vacuum degree of -0.08MPa to -0.1MPa to obtain a fire-resistant silicone sealant with low smoke emission.
[0077] The obtained low smoke fireproof silicone sealant was subjected to performance tests: the tensile strength was tested according to the method specified in GB / T528-2009; the oxygen index was tested according to the method specified in GB / T 2406-2008; the flame retardancy was tested according to the method specified in GB / T2408-2008; the smoke density level was tested according to the method specified in GB / T 8627-2007. The specific test results are shown in Table 1.
[0078] Embodiment 2
[0079] The preparation method of low smoke-generating fireproof silicone sealant comprises the following preparation steps:
[0080] 201) A modified layered MgAl double hydroxide is prepared, the preparation process comprising:
[0081] A21) mixing magnesium nitrate, aluminum nitrate and ZrOCl2·8H2O solution in a molar ratio of 3:1:1, heating to 80° C. under a nitrogen atmosphere, controlling the pH to 9-10, reacting for 10 h, and obtaining a suspension;
[0082] A22) transferring the suspension into a stainless steel autoclave with a Teflon liner, reacting at 600° C. for 5 h, cooling to room temperature, filtering, washing, and drying to obtain Zr / MgAl-LDH;
[0083] A23) Stearic acid and Zr / MgAl-LDH are added to deionized water in a mass ratio of 3:2, the pH is adjusted to 7, the reaction is carried out at 80° C. for 10 hours, the mixture is filtered and washed multiple times, and dried to obtain a modified layered MgAl double hydroxide.
[0084] 202) preparing modified nano composite expanded graphite, the preparation steps comprising:
[0085] B21) washing expanded graphite, washing 30 parts of expanded graphite with 120 parts of deionized water to remove impurities on the surface of the expanded graphite, drying at 60° C. for 6 h, placing the dried expanded graphite in a mixed solution of anhydrous ethanol and deionized water, and ultrasonically treating to obtain a suspension;
[0086] B22) slowly adding ammonia solution into the suspension, adjusting the pH value to 8-9, and obtaining an expanded graphite suspension;
[0087] B23) adding ethyl orthosilicate slowly dropwise to the suspension, stirring and reacting at 55° C. for 6 h, filtering and washing with ethanol several times until neutral, and drying at 60° C. for 12 h to obtain nanocomposite expanded graphite;
[0088] B24) adding deionized water to the nanocomposite expanded graphite, stirring to obtain a nanocomposite expanded graphite slurry, dissolving a silane coupling agent in a small amount of anhydrous ethanol, pouring the mixture into the nanocomposite expanded graphite slurry, stirring to obtain a modified nanocomposite expanded graphite, wherein the mass ratio of the nanocomposite expanded graphite: the silane coupling agent: the ethanol: the aqueous solution is 1:0.06:0.2:3; wherein the coupling agent is hexadecyltrimethoxysilane; the particle size of the expanded graphite is 200 μm; and the amount of ethyl orthosilicate added is 3wt% of the expanded graphite.
[0089] 203) mixing the modified layered MgAl double metal hydroxide and the modified nano-composite expanded graphite to obtain a composite flame retardant, wherein the mass ratio of the modified layered MgAl double metal hydroxide to the modified nano-composite expanded graphite is 80:20;
[0090] 204) According to the weight ratio, 100 parts of α, ω-dihydroxy polydimethylsiloxane, 10 parts of dimethyl silicone oil, 5 parts of inorganic filler and 10 parts of porcelain filler are added into a planetary machine, and dehydrated for 90 minutes at 110° C. and a vacuum degree of -0.08 MPa to -0.1 MPa to obtain a base material;
[0091] 205) The base material is cooled to room temperature, 30 parts of composite flame retardant, 0.05 parts of catalyst, 5 parts of cross-linking agent and 4 parts of silane coupling agent are added, mixed, and stirred for 90 minutes under a vacuum degree of -0.08MPa to -0.1MPa to obtain a fire-resistant silicone sealant with low smoke emission.
[0092] The obtained low smoke fireproof silicone sealant was subjected to performance tests: the tensile strength was tested according to the method specified in GB / T528-2009; the oxygen index was tested according to the method specified in GB / T 2406-2008; the flame retardancy was tested according to the method specified in GB / T2408-2008; the smoke density level was tested according to the method specified in GB / T 8627-2007. The specific test results are shown in Table 1.
[0093] Embodiment 3
[0094] The preparation method of low smoke-generating fireproof silicone sealant comprises the following preparation steps:
[0095] 301) preparing a modified layered MgAl double hydroxide, the preparation process comprising:
[0096] A31) mixing magnesium nitrate, aluminum nitrate and ZrOCl2·8H2O solution in a molar ratio of 3:1:3, heating to 80° C. under a nitrogen atmosphere, controlling the pH to 9-10, reacting for 10 h, and obtaining a suspension;
[0097] A32) transferring the suspension into a stainless steel autoclave with a Teflon liner, reacting at 600° C. for 5 h, cooling to room temperature, filtering and washing for multiple times, and drying to obtain Zr / MgAl-LDH;
[0098] A33) Stearic acid and Zr / MgAl-LDH are added to deionized water in a mass ratio of 3:2, the pH is adjusted to 7, the reaction is carried out at 80° C. for 10 h, and the reaction is filtered, washed, and dried to obtain a modified layered MgAl double hydroxide.
[0099] 302) preparing modified nano composite expanded graphite, the preparation steps comprising:
[0100] B31) washing the expanded graphite to remove impurities on the surface of the expanded graphite, drying at 60° C. for 6 h, placing the dried expanded graphite in a mixed solution of anhydrous ethanol and deionized water, and ultrasonically treating the dried expanded graphite to obtain a suspension;
[0101] B32) adding ammonia solution into the suspension, adjusting the pH value to 8-9, and obtaining an expanded graphite suspension;
[0102] B33) adding ethyl orthosilicate slowly dropwise to the suspension, stirring and reacting at 55° C. for 6 h, filtering and washing with ethanol several times until neutral, and drying at 60° C. for 12 h to obtain nanocomposite expanded graphite;
[0103] B34) adding deionized water to the nanocomposite expanded graphite and stirring to obtain a nanocomposite expanded graphite slurry, dissolving a silane coupling agent in a small amount of anhydrous ethanol, pouring the solution into the nanocomposite expanded graphite slurry and stirring to obtain a modified nanocomposite expanded graphite, wherein the mass ratio of the nanocomposite expanded graphite: the silane coupling agent: the ethanol: the aqueous solution is 1:0.02:0.4:3; wherein the coupling agent is one of hexadecyltrimethoxysilane, dodecyltrimethoxysilane or cycloalkylsilane; the particle size of the expanded graphite is 200-300 μm; and the amount of ethyl orthosilicate added is 2wt% of the expanded graphite.
[0104] 303) mixing the modified layered MgAl double metal hydroxide and the modified nano-composite expanded graphite to obtain a composite flame retardant, wherein the mass ratio of the modified layered MgAl double metal hydroxide to the modified nano-composite expanded graphite is 60:40;
[0105] 304) According to the weight ratio, 140 parts of α, ω-dihydroxy polydimethylsiloxane, 40 parts of dimethyl silicone oil, 20 parts of inorganic filler and 80 parts of porcelain filler are added into a planetary machine, and dehydrated for 160 minutes at 140° C. and a vacuum degree of -0.08 MPa to -0.1 MPa to obtain a base material;
[0106] 305) The base material is cooled to room temperature, 80 parts of composite flame retardant, 0.2 parts of catalyst, 15 parts of cross-linking agent and 6 parts of silane coupling agent are added, mixed, and stirred for 180 minutes under a vacuum degree of -0.08MPa to -0.1MPa to obtain a fire-resistant silicone sealant with low smoke emission.
[0107] The obtained low smoke fireproof silicone sealant was subjected to performance tests: the tensile strength was tested according to the method specified in GB / T528-2009; the oxygen index was tested according to the method specified in GB / T 2406-2008; the flame retardancy was tested according to the method specified in GB / T2408-2008; the smoke density level was tested according to the method specified in GB / T 8627-2007. The specific test results are shown in Table 1.
[0108] Embodiment 4
[0109] The difference between this embodiment and the first embodiment is that the ceramic filler is modified glass fiber, and the treatment process of the modified glass fiber is as follows:
[0110] After mixing glass fiber and water glass, stirring at a temperature of 55°C for 60 minutes, filtering and drying to obtain modified glass fiber;
[0111] Among them, the mass ratio of glass fiber to water glass is 1:0.5;
[0112] The particle size of the glass fiber is 5 μm.
[0113] Embodiment 5
[0114] The difference between this embodiment and the first embodiment is that the inorganic filler is a modified inorganic filler, and the preparation method of the modified inorganic filler comprises:
[0115] After the inorganic filler is mixed with the silane coupling agent and ethanol, the mixture is stirred at a temperature of 50-60° C. for 60 minutes, filtered and dried to obtain a modified inorganic filler; wherein the mass ratio of the inorganic filler: the silane coupling agent: the ethanol is 1:0.3:2; the inorganic filler is nano-calcium carbonate, and the silane coupling agent is KH570.
[0116] Comparative Example 1
[0117] The difference between this comparative example and Example 4 is that the ceramic filler is different, and the glass fiber of this comparative example is not modified.
[0118] Comparative Example 2
[0119] The difference between this comparative example and Example 1 is that the composite flame retardant is different, and the modified layered MgAl double metal hydroxide is not added in this comparative example.
[0120] Comparative Example 3
[0121] The difference between this comparative example and Example 1 is that the composite flame retardant is different, and the modified nano composite expanded graphite is not added in this comparative example.
[0122] Comparative Example 4
[0123] The difference between this comparative example and Example 1 is that layered MgAl double metal hydroxide and expanded graphite are added.
[0124] Comparative Example 5
[0125] The difference between this comparative example and Example 1 is that the mass ratio of the modified layered MgAl double metal hydroxide to the modified nano-composite expanded graphite is 30:70.
[0126] Comparative Example 6
[0127] The difference between this comparative example and Example 1 is that the amount of the porcelain-forming filler is 100 parts.
[0128] Table 1 Test results of low smoke fireproof silicone sealant
[0129]
[0130]
[0131] Compared with Example 1, Example 4 further modifies the ceramic material, and improves the compatibility between the filler and the sealant matrix, thereby improving the dispersibility of the filler and further improving the flame retardant and mechanical properties of the obtained sealant.
[0132] Compared with Example 1, Example 5 further modifies the inorganic filler, thereby improving the compatibility between the inorganic filler and the sealant matrix, thereby improving the dispersibility of the filler and improving the flame retardant and mechanical properties of the obtained sealant.
[0133] Compared with Example 4, Comparative Example 1 does not modify the porcelain-forming material. Compared with Example 4, the flame retardant performance, oxygen index and tensile strength of the fireproof sealant obtained in Comparative Example 1 are reduced, and the smoke density level is much higher than that in Example 1.
[0134] Comparative Example 2 and Comparative Example 3 are respectively without adding modified inorganic flame retardant and without adding modified nano-composite expanded graphite. The mechanical properties of the prepared fireproof sealant are lower than those of Example 1, the flame retardant performance and oxygen index are reduced, and the smoke density level is higher than that of Example 1, indicating that the modified inorganic flame retardant and the modified nano-composite expanded graphite have a synergistic effect, which improves the flame retardant performance and smoke suppression effect of the obtained sealant while maintaining good mechanical properties.
[0135] Compared with Example 1, Comparative Example 4 does not modify the inorganic flame retardant and the expanded graphite. The mechanical properties of the fire-retardant sealant prepared in Comparative Example 4 are lower than those in Example 1, the oxygen index and the flame retardant grade are reduced, and the smoke density grade is higher than that in Example 1, indicating that the modified inorganic flame retardant and the modified nano-expanded graphite material can be evenly dispersed in the sealant matrix, and there is a synergistic effect between the two, which helps to form a dense carbonized layer, hinders the transfer of heat and oxygen, further enhances the overall flame retardant effect, and reduces the smoke emission.
[0136] Compared with Example 1, the mass ratio of the modified layered MgAl double metal hydroxide and the modified nano-composite expanded graphite in Comparative Example 5 is less than that in Example 1. Compared with Example 1, the index and the flame retardant level are reduced, and the smoke density level is higher than that in Example 1, indicating that the modified inorganic flame retardant and the modified nano-expanded graphite material improve the flame retardant and smoke suppression effects of the sealant under a certain ratio.
[0137] Compared with Example 1, the amount of ceramic filler added in Comparative Example 6 exceeds that in Example 1. Compared with Example 1, the oxygen index and flame retardancy level decrease, and the smoke density level is higher than that in Example 1, indicating that too much ceramic filler is added, which affects the flame retardancy and mechanical properties of the sealant and increases the smoke generated during combustion.
[0138] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A fire-resistant silicone sealant with low smoke emission, characterized in that: According to weight percentage, including: 100-140 parts of α,ω-dihydroxy polydimethylsiloxane, 10-40 parts of dimethyl silicone oil, 30-80 parts of composite flame retardant, 5-20 parts of inorganic filler, 10-80 parts of ceramic filler, 0.05-0.2 parts of catalyst, 5-15 parts of crosslinking agent and 4-6 parts of silane coupling agent; The composite flame retardant consists of modified layered MgAl double metal hydroxide and modified nano composite expanded graphite.
2. The low smoke-generating fireproof silicone sealant according to claim 1, characterized in that: The mass ratio of the modified layered MgAl double metal hydroxide to the modified nano-composite expanded graphite is (60-80):(20-40).
3. The low smoke-generating fireproof silicone sealant according to claim 1, characterized in that: The preparation process of modified layered MgAl double hydroxide includes: Mix magnesium nitrate, aluminum nitrate and ZrOCl2·8H2O solution in a molar ratio of 3:1:(1-3), heat to 80°C under a nitrogen atmosphere, control the pH to 9-10, react for 10 hours, and obtain a suspension; The suspension was transferred to an autoclave, reacted at 600°C for 5 h, cooled to room temperature, filtered, washed, and dried to obtain Zr / MgAl-LDH; Stearic acid and Zr / MgAl-LDH were added to deionized water with a mass ratio of 3:
2. The pH was adjusted to 7. The mixture was reacted at 80° C. for 10 h. The mixture was filtered, washed, and dried to obtain a modified layered MgAl double hydroxide.
4. The low smoke-generating fireproof silicone sealant according to claim 1, characterized in that: The preparation steps of modified nano composite expanded graphite include: The expanded graphite is washed and dried, and the dried expanded graphite is placed in a mixed solution of anhydrous ethanol and deionized water, and subjected to ultrasonic treatment to obtain a suspension; Adding an ammonia solution to the suspension and adjusting the pH value to 8-9 to obtain an expanded graphite suspension; Slowly drop ethyl orthosilicate into the suspension, stir and react at 55°C for 6 hours, filter and wash with ethanol until neutral, and dry to obtain nanocomposite expanded graphite; Deionized water is added to the nano-composite expanded graphite, and the mixture is stirred to obtain a nano-composite expanded graphite slurry. A silane coupling agent is dissolved in a small amount of anhydrous ethanol, and the mixture is poured into the nano-composite expanded graphite slurry, and the mixture is stirred to obtain a modified nano-composite expanded graphite.
5. The low smoke-generating fireproof silicone sealant according to claim 4, characterized in that: The coupling agent is one of hexadecyltrimethoxysilane, dodecyltrimethoxysilane or cycloalkylsilane.
6. The low smoke-generating fireproof silicone sealant according to claim 4, characterized in that: The particle size of the expanded graphite is 200-300 μm; the amount of ethyl orthosilicate added is 1-3 wt % of the expanded graphite.
7. The low smoke-generating fireproof silicone sealant according to claim 4, characterized in that: The mass ratio of nano-composite expanded graphite: silane coupling agent: ethanol: aqueous solution is 1: (0.02-0.06): (0.2-0.4): (3-5).
8. The low smoke-generating fireproof silicone sealant according to claim 1, characterized in that: The inorganic filler is a modified inorganic filler, and the preparation method of the modified inorganic filler includes: The inorganic filler is mixed with a silane coupling agent and ethanol, stirred at a temperature of 50-60° C. for 60 minutes, filtered and dried to obtain a modified inorganic filler; wherein the mass ratio of the inorganic filler: the silane coupling agent: the ethanol is 1: (0.1-0.3): (2-5). Preferably, the silane coupling agent is one of KH550, KH60 or KH570.
9. The low smoke-generating fireproof silicone sealant according to claim 1, characterized in that: The ceramic filler is modified glass fiber, and the modified glass fiber processing process is: After mixing glass fiber and water glass, stirring at a temperature of 50-60°C for 60 minutes, filtering and drying to obtain modified glass fiber; Wherein, the mass ratio of glass fiber to water glass is 1:(0.1-0.3); The particle size of the glass fiber is 0.1-10 μm.
10. A method for preparing a low-smoke fire-resistant silicone sealant according to any one of claims 1 to 9, characterized in that: The method comprises the following preparation steps: According to the weight ratio, α, ω-dihydroxy polydimethylsiloxane, dimethyl silicone oil, inorganic filler and ceramic filler are added into a planetary machine, and dehydrated for 90 to 160 minutes at 110° C. to 140° C. and a vacuum degree of -0.08 MPa to -0.1 MPa to obtain a base material; The base material is cooled to room temperature, and a composite flame retardant, a catalyst, a cross-linking agent and a silane coupling agent are added and mixed, and stirred for 90 to 180 minutes under a vacuum degree of -0.08 MPa to -0.1 MPa to obtain a fire-resistant silicone sealant with low smoke emission.
Citation Information
Patent Citations
A method for preparing a ceramicized fire-retardant silicone sealant
CN110003844B
A kind of silicone fireproof sealant for building
CN117965130B
Composite fireproof adhesive and preparation method thereof
CN118772804A